Factors Associated with Low Socioeconomic Status Predict Poor Postoperative Follow-up after Meningioma Resection - Nayeri, Arash; Brinson, Philip R.; Weaver, Kyle D.; Thompson, Reid C.; Chambless, Lola B. (Journal of Neurological Surgery Part B: Skull Base, 2016)
Objectives To quantify the rates of loss of follow-up after meningioma resection and to identify any key demographical associations.Design Retrospective cohort.Setting Vanderbilt University Medical Center, 2001–2013.Participants A total of 281 patients surgically treated for an intracranial meningioma at a single institution between 2001 and 2013.Main Outcome Measures Patient clinical follow-up within the first postoperative year.Results A history of tobacco use (p < 0.0001), ongoing alcohol abuse at time of presentation (p = 0.0014), Medicaid coverage (p < 0.0001), and lack of a college degree (p < 0.0001) were all found to be predictors of loss of follow-up at a statistically significant level.Conclusions Several factors associated with low socioeconomic status are predictors of poor clinical follow-up after meningioma resection. The health risk of poor follow-up in this patient population is significant, and increased measures are needed to ensure regular appointment attendance.
Keywords: meningioma; follow-up; socioeconomic status; tobacco